Apparent umpolung reactivity of indole through [Au]-catalysed cyclisation and lewis-acid-mediated allylation - Shinde, Mahesh H.; Ramana, Chepuri V. (Chemistry-A European Journal, 2020)
The sequential functionalization of indole C2 and C3 in an umpolung fashion was executed with a predesigned substrate and choice of reagents. The developed method comprises gold-catalysed alkynol cycloisomerisation/intramolecular addition of C2 of indole and subsequent BF3.OEt2-mediated regioselective C3 allylation, resulting in the synthesis of the functionalized indoloisoquinolinone scaffold. The reaction involves 5-endo-alkynol cycloisomerisation and the dearomative addition of indole C2 to the intermediate oxocarbenium cation, which results in two equilibrating fused and spiropentacyclic intermediates, which upon treatment with allyl silane in the presence of BF3.OEt2, undergo selective indole C3 allylation. Other nucleophiles, such as hydride, azide and indole, were also found to be compatible with this process.
Keywords: Allylation; cyclization; domino reactions; Gold; umpolung